Enhanced phytoremediation of domestic wastewater using lepironia articulata, monochoria vaginalis and typha angustifolia: Comparative performance and efficacy - Firdaus, Ismail; Abdul Syukor, Abd Razak; Ali Zainal-Abidin, Mohd Termizi; Muhammad Amirul Syafiq, Nasaruddin; Suryati, Sulaiman (Penerbit UMP, 2024)
The generation and composition of wastewater are influenced by various factors, including human behavior, lifestyle, and industrial activities. Household waste comprises both solid and liquid components, which can be managed and treated through sustainable practices and advanced technologies. Phytoremediation, using aquatic plants, offers an environmentally friendly method to treat wastewater and remove heavy metals, which are significant inorganic contaminants. This study investigates the efficacy of three aquatic plants—Monochoria vaginalis, Typha angustifolia, and Lepironia articulata—in phytoremediating domestic wastewater collected from an oxidation pond in Pasir Gudang, Johor Bahru. Over an 11-week period, in situ and ex situ experiments were conducted to measure the reduction in concentrations of heavy metals (Copper, Chromium, Iron, Lead, and Zinc) and other parameters (BOD, COD, TSS, Turbidity, and pH). The results demonstrate that all three plants effectively reduced the concentrations of heavy metals and other parameters. Copper, Iron, Lead, and Zinc were completely removed by all three plants, with removal percentages reaching 100%. Monochoria vaginalis showed the highest removal efficiency for Chromium (70%) and COD (97%). Lepironia articulata exhibited the highest removal efficiencies for BOD (85%), TSS (92%), and Turbidity (97%). Typha angustifolia also achieved significant removal of pollutants, particularly showing strong performance in removing heavy metals, with BOD reduction reaching 83% and COD reduction at 90%. These findings confirm the potential of Monochoria vaginalis, Typha angustifolia, and Lepironia articulata as effective phytoremediation agents for treating domestic wastewater and mitigating environmental pollution.